IMPLEMENTASI KEBIJAKAN PROGRAM BERAS SEJAHTERA DI KABUPATEN PANGANDARAN - Supriatna, Encup; Ristanti, Rira (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2018)
Raskin/Rastra is one of the programs the Government does Indonesia. The program is a program of aid from Government to society in the form of subsidized rice intended for low-income communities. The program is carried out in an effort to improve access in meeting the basic rights of the underprivileged of the community towards food needs. This research aims to analyze how the implementation of a policy of killing raskin/rastra village Babakan and to know the obstacles and constraints faced in the distribution and management of Raskin/Rastra village Babakan Sub-district Pangandaran The Regency Of Pangandaran. In the study of public policy Implementation theory with George c. Edward III. In this approach, there are four variables to measure the success of the implementation of the policy, namely communication, resources, disposition, and bureaucratic structure. Based on the results obtained by researchers concluded that the implementation of a policy of killing poor Rice/rice prosperous village Babakan Sub-district Pangandaran The Regency Of Pangandaran has not run optimally